Stereotactic Radiosurgery for Intracranial Noncavernous Sinus Benign Meningioma: International Stereotactic Radiosurgery Society Systematic Review, Meta-Analysis and Practice Guideline. Issue 5 (28th May 2020) - Marchetti, Marcello; Sahgal, Arjun; De Salles, Antonio A F; Levivier, Marc; Ma, Lijun; Paddick, Ian; Pollock, Bruce E; Regis, Jean; Sheehan, Jason; Suh, John H; Yomo, Shoji; Fariselli, Laura
Abstract: BACKGROUND: Stereotactic radiosurgery (SRS) for benign intracranial meningiomas is an established treatment. OBJECTIVE: To summarize the literature and provide evidence-based practice guidelines on behalf of the International Stereotactic Radiosurgery Society (ISRS). METHODS: Articles in English specific to SRS for benign intracranial meningioma, published from January 1964 to April 2018, were systematically reviewed. Three electronic databases, PubMed, EMBASE, and the Cochrane Central Register, were searched. RESULTS: Out of the 2844 studies identified, 305 had a full text evaluation and 27 studies met the criteria to be included in this analysis. All but one were retrospective studies. The 10-yr local control (LC) rate ranged from 71% to 100%. The 10-yr progression-free-survival rate ranged from 55% to 97%. The prescription dose ranged typically between 12 and 15 Gy, delivered in a single fraction. Toxicity rate was generally low. CONCLUSION: The current literature supporting SRS for benign intracranial meningioma lacks level I and II evidence. However, when summarizing the large number of level III studies, it is clear that SRS can be recommended as an effective evidence-based treatment option (recommendation level II) for grade 1 meningioma.